2009
DOI: 10.1007/s15010-009-8249-6
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Intra-Abdominal Flora in Critically Ill Patients with Secondary and Tertiary Abdominal Sepsis

Abstract: The composition of the intra-abdominal flora found in critically ill patients with abdominal sepsis varies depending on the location of the perforation. The efficacy of combined surgical and antibiotic treatment was 87% in 4 weeks for AGNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
95
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 19 publications
12
95
1
13
Order By: Relevance
“…The majority of polymicrobial fungal IAIs are caused by Candida albicans (12,13). However, IAIs caused by non-albicans Candida (NAC) species are becoming more common (14).…”
mentioning
confidence: 99%
“…The majority of polymicrobial fungal IAIs are caused by Candida albicans (12,13). However, IAIs caused by non-albicans Candida (NAC) species are becoming more common (14).…”
mentioning
confidence: 99%
“…As much as 60%, the anaerobic bacteria can be isolated in these infections. However, if there isn't any predisposing factor as strangulated hernia, these infections rarely observed [3,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…De Ruiter et al [6] have reported that isolated microorganism from 69% of cases with sepsis in abdominal fluid samples, and 70% of the isolated microorganism were mixed microorganisms that including anaerobic bacteria. Anaerobic and facultative anaerobic bacteria were commonly isolated in the peritoneal fluid samples by Stone et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…These include persisting peritonitis despite adequate surgical and initial antimicrobial therapy [62], "persistent and tertiary chronic" peritonitis with distinct changes in immuno-responsiveness [63], and where there has been a prolonged course with microbiological shift from aerobic gram-negative bacteria towards gram-positive bacteria over time [64]. In a study of 69 patients with secondary peritonitis among whom 15 patients (22%) developed tertiary peritonitis, transition to tertiary peritonitis was associated with a higher Mannheim Peritonitis Index at the initial operation, higher severity of illness scores and CRP levels on the second postoperative day, higher relaparotomy rates with increased mortality (60% vs. 9%), and a longer ICU length of stay [65].…”
Section: Tertiary Peritonitismentioning
confidence: 99%